Kriminalisasi Terorisme di Indonesia dalam Era Globalisasi - Muhammad Arif Setiawan (Jurnal Hukum IUS QUIA IUSTUM, 2002)
Criminalistiaon of terrorism in Indonesia is certainly related to the global dinamization process occurred recently. Viewed substantially the cnme of terrorism for specifically international terronsm actually is not the single crime because it can be a transnational crime. Even through seeing the terronsm ofcrime correlated to the crimeSj theprocess ofcn'minalization from the various of aspects mustbe determined comprehen sively.